SMART KAMPUNG SEBAGAI WUJUD KEMAJUAN SISTEM ADMINISTRASI DAN MANAJEMEN DI DESA KETAPANG, KECAMATAN KALIPURO, KABUPATEN BANYUWANGI - Retno Wulan Sekarsari; Tedy Winarno (JPSI (Journal of Public Sector Innovations), 2018)
The objective of this research is to learn about the implementation system of œSmart Kampung Program at Ketapang Village and its methods of publication to all over Indonesia.This IT-based public service and human resource enhancement program, called œSmart Kampung, is an innovation made by the District Government of Banyuwangi. This program represents the commitment of the district government to bring public service to the most accessible level for the people of Banyuwangi. Since most of them live far from the urban area, which is the governance base or center, the District Government of Banyuwangi set village offices as the centers of public service directly integrated with the District Government. By doing so, the District Government facilitates the society and make them aware of the importance of IT. In addition to being a facility to enhance public service, Smart Kampung Program can also serve as a facility to improve the quality of human resources and the peoples economy, as the village governments are required to empower their respective villages potentials.There are a number of ways utilized by the District Government of Banyuwangi and Smart Kampung villagesto socialize this program, such as information sharing in seminars, local leaders meeting, and social media. By doing so, they hope they can inspire regions with similar issues to implement Smart Kampung Program so that the goal to have equal welfare level in all villages in Indonesia can be achieved.